2013
DOI: 10.1097/aln.0b013e3182a8a998
|View full text |Cite
|
Sign up to set email alerts
|

Exome Sequencing Reveals Novel Rare Variants in the Ryanodine Receptor and Calcium Channel Genes in Malignant Hyperthermia Families

Abstract: Background About half of malignant hyperthermia (MH) cases are associated with skeletal muscle ryanodine receptor 1 (RYR1) and calcium channel, voltage-dependent, L type, α1S subunit (CACNA1S) gene mutations, leaving many with an unknown cause. We chose to apply a sequencing approach to uncover causal variants in unknown cases. Sequencing the exome, the protein-coding region of the genome, has power at low sample sizes and identified the cause of over a dozen Mendelian disorders. Methods We considered four f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 40 publications
3
58
0
Order By: Relevance
“…Thus initially RYR1 mutations were described in individuals susceptible to malignant hyperthermia (MHS) [17,18]. RYR1 mutations associated with MHS are typically heterozygous missense substitutions [19][20][21]. Subsequently RYR1 mutations were described in the context of a variety of histological subtypes of congenital myopathies including central core disease, minicore/centronuclear myopathy with external ophthalmoplegia, centronuclear myopathy and congenital fibre-type disproportion [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Thus initially RYR1 mutations were described in individuals susceptible to malignant hyperthermia (MHS) [17,18]. RYR1 mutations associated with MHS are typically heterozygous missense substitutions [19][20][21]. Subsequently RYR1 mutations were described in the context of a variety of histological subtypes of congenital myopathies including central core disease, minicore/centronuclear myopathy with external ophthalmoplegia, centronuclear myopathy and congenital fibre-type disproportion [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Initial efforts using whole exome sequencing have largely resulted in validation of RYR1 mutations as the primary cause of disease in the majority of cases [11,16]. These studies have also revealed many RYR1 variants of unknown significance that require further validation in order to be listed as pathogenic.…”
Section: How Is the Disorder Treated?mentioning
confidence: 99%
“…It is now clear that RYR1-related myopathies are the most common nondystrophic muscle conditions of childhood and that the clinical spectrum for the disorders is vast [36,37]. One important issue to emerge is how to interpret identified sequence variants in RYR1 that are of uncertain pathogenicity [11,16]. AS RYR1 mutations are associated with such a broad range of disease, most novel variants identified in RYR1 have the potential of causing disease.…”
Section: What Are Key Current Issues Related To the Disease?mentioning
confidence: 99%
“…Drs. Hopkins and Kim 41 analyzed RYR1 and CACNA1S variants identified using WES in 5,379 of individuals as part of the National Heart, Lung, and Blood Institute (NHLBI) Grand Opportunity (GO) Exome Sequencing Project (ESP). Their analyses showed that RYR1 is more genetically diverse than 74–79% of other genes in European-Americans and African Americans, while CACNA1S is more genetically diverse than 77–82% of other genes in these cohorts.…”
Section: Relationship Of Mh With Ehi Er and Statin Myopathiesmentioning
confidence: 99%